Computing trends of public cloud IT services applied in businesses: a systematic review - Chávez Cerna, Luis Adonis (2023)
Cloud services, have become one of the main technological trends in information thanks to the great advantages they offer users in the business field. In this regard, a systematic review was carried out using the PRISMA methodology. Documents in the Scopus, SciELO, and Google Scholar databases were analyzed between 2017 and 2022, and inclusion and exclusion criteria were used to select 13 relevant articles from the 65 documents analyzed. The review highlights that Microsoft Azure and AWS are the cloud services that have the greatest tendency to be used by companies due to their ease of use and the facilities offered by companies to obtain credits on their platform and be able to use them. Additionally, these services are also applied in other fields such as medicine, education, accounting, and industry.